Holocene slip-rate on the Gowk strike-slip fault and implications for the distribution of tectonic strain in eastern Iran - Walker, RT; Talebian, M; Sloan, R; Rasheedi, A; Fattahi, M; Bryant, C (2010)
We provide the first quantitative estimate of the Holocene slip-rate on the Gowk strike-slip fault in eastern Iran. The main active strand of the fault cuts lakebed sediments within the South Golbaf pull-apart basin. Numerous channels incised into the palaeolake surface are displaced right-laterally by 30 ± 5 m at the fault. Radiocarbon dating of two terrestrial wood fragments constrains the lake desiccation at a maximum of 7.9 ± 0.1 cal ka BP, from which we estimate a minimum slip-rate for the Gowk fault of 3.8 ± 0.7 mm yr-1. This estimate indicates that the Gowk fault is one of the most important structures in the accommodation of regional tectonic strain in eastern Iran. The Gowk fault has generated five destructive earthquakes in the past 30 yr. At a minimum rate of 3.8 ± 0.7 mm yr-1 the average interval between earthquakes, assuming that the fault typically fails in events involving ~3 m of slip, will be 660-960 yr. The southern ~90 km of the Gowk fault (the Sarvestan segment) has no record of historical earthquakes and constitutes a considerable remaining hazard in this region. Our estimated rate is consistent with geodetic measurements of deformation across the same area and hence suggests that the slip-rate on the Gowk fault has been constant since at least ~8 ka ago. Determining whether or not Holocene and late Quaternary variations in slip-rate occur in general across eastern Iran requires similar quantitative studies of fault slip-rate across the major faults of eastern Iran. © 2010 The Authors Journal compilation © 2010 RAS.